Geospasial Intelijen Menggunakan Teknologi Satelit untuk Identifikasi Potensi Sumber Daya Energi dan Meningkatkan Keamanan Nasional - Luwis Surani Haloho; Sukendra Martha; Asep Adang Supriyadi; Annisa Harum Sadewa (Departement of Mathematics Education, 2024)
Geospatial intelligence all activities involved in planning, collecting, processing, analyzing, exploiting, and disseminating spatial information obtained to gain intelligence about the national security or operational environment, and providing visual representation this knowledge. Geospatial intelligence plays important role in disaster monitoring by providing critical insight information that supports disaster risk reduction and management. Addition to monitoring disasters geospatial intelligence indispensable for monitoring natural resources and potential of each geographic area to optimize all natural resources. Last also plays role in law enforcement, for example the sea where sea is monitored and found violations can harm many parties so that the importance of geospatial intelligence is very helpful to various parties of course also for defense, state security. This research is a systematic literature review that explains the role of geospatial intelligence dealing with military and non-military threats, namely Geospatial Information Systems combined with NASA MERRA-2 hourly global wind speed data and DTU Global Wind Atlas that spatially resolved to characterize the potential for onshore wind energy globally in order to optimally obtain the potential for geography in non-military threats, the concept of military operations aims to secure a country's sea by involving various technologies and intelligence to protect rights and resources